Kinematic and dynamic synthesis of a balance training machine for rehabilitation - Koh, Shirong. (2012)
This project aims to synthesize a design procedure to develop a reliable balance training machine that is capable of helping stoke patients who suffers from weak muscle and less sensation to improve their balance ability. The machine is to provide sudden perturbation and rocking motions to simulate the effects on Mass Rapid Transit (MRT) and the situation of slippage. Since perturbations and acceleration is concerned, it is imperative to realize the importance of the kinematic and dynamic characteristics of the system. Hence a critical and substantial portion was dedicated to analyze them.